Predictors for a positive QuantiFERON-TB-Gold test in BCG-vaccinated adults with a positive tuberculin skin test - Harsh Chawla; Mark N. Lobato; Lynn E. Sosa; Richard ZuWallack (Elsevier, 2012)
Summary: Background: Prevention of tuberculosis (TB) in the United States usually involves testing for latent tuberculosis infection (LTBI) with a tuberculin skin test (TST), followed by offering therapy to those who have a positive test result. QuantiFERON-TB Gold assay (QFT-G) is more specific for infection with Mycobacterium tuberculosis than the TST, especially among persons vaccinated with bacillus Calmette-Guérin, thereby reducing the number of false positive tests. Methods: Adults referred to a pulmonary clinic for a positive TST result were tested with QFT-G. We assessed factors for having a positive QFT-G. Results: Among 100 adults who were BCG-vaccinated and had a positive TST result, 30 (30%) had a positive result using QFT-G. Persons from high-incidence countries were 8.2 times more likely to have a positive QFT-G result compared with persons from low-incidence countries (46% versus 9%). Using logistic regression to assess QFT-G positivity, strong predictors included having an abnormal chest radiograph consistent with healed TB, a TST induration of ≥16 mm, and birth in a high-incidence country. Conclusion: Use of QFT-G assay following a positive TST result further identifies persons who would most benefit from treatment for LTBI. Keywords: Tuberculosis, Latent tuberculosis infection, Diagnosis, Treatment, Prevention